Use of antibiotics by urban and rural residents in Heilongjiang Province, China: cross‐sectional study. Issue 12 (12th October 2015) - Gu, Jiarui; Zhao, Jizi; Huang, Ying; Yang, Weidong; Ren, Zheng; Li, Wenjing; Fan, Yuzhuo; Zhang, Qiao; Zhang, Fengmin; Fu, Yingmei
Abstract: Objective: To identify and compare the factors affecting the knowledge of, attitude towards and use of antibiotics between urban and rural residents in China. Methods: A total of 3631 urban and rural residents in Heilongjiang Province, China, were selected using random sampling. Questionnaires recorded demographic characteristics and participant knowledge of, attitude towards and use of antibiotics. The responses of rural and urban residents were compared, and logistic regression analysis was applied to identify the factors that may contribute to the knowledge of, attitude towards and use of antibiotics. Results: The majority of the participants (>60%) were aware that antibiotics could be used to treat bacterial infections and that bacteria could be resistant to antibiotics. However, only roughly half (40–60%) of the participants were aware that bacterial resistance to antibiotics had become a problem in China. Urban participants reported a more adequate knowledge of, attitude towards and use of antibiotics than rural participants. Logistic regression analysis indicated that urban residency, female gender and level of education were associated with knowledge of, attitude towards and use of antibiotics. Conclusions: Within our sample in Heilongjiang Province, the knowledge of, attitude towards and use of antibiotics were suboptimal in roughly half of all urban and rural residents, but better in urban than in rural residents. Targeted interventions to educate rural residents in particular may reduce the misuse of antibiotics.